2019
DOI: 10.1002/ejp.1499
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between male norm beliefs, pain‐related beliefs and behaviours: An online questionnaire study

Abstract: Background Gender beliefs help explain the variation found in pain among men and women. Gender norms and expectations are thought to affect how men and women report and express pain. However, less is known about how such beliefs are related to pain outside of laboratory settings. The aim of this study was therefore to consider the relationship between beliefs in male role norms, pain and pain behaviours in men and women. Methods An online questionnaire study was conducted. A total of 468 adults (352 women), wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“… 129 Considering gender as a biopsychosocial construct, 130 there is reason to suspect that men and women experience pain and substance use differently. For example, masculine norms may influence which pain-related behaviors are most common or accessible to men, 131 which is consistent with a larger literature indicating that men are more likely than women to cope with pain and anxiety by using externalizing strategies. 132 , 133 Thus, future studies that consider pharmacokinetic properties of prescription opioids and alcohol should examine sex as a biological variable, and research that investigates psychosocial and behavioral constructs should explore gender differences.…”
Section: Discussionsupporting
confidence: 80%
“… 129 Considering gender as a biopsychosocial construct, 130 there is reason to suspect that men and women experience pain and substance use differently. For example, masculine norms may influence which pain-related behaviors are most common or accessible to men, 131 which is consistent with a larger literature indicating that men are more likely than women to cope with pain and anxiety by using externalizing strategies. 132 , 133 Thus, future studies that consider pharmacokinetic properties of prescription opioids and alcohol should examine sex as a biological variable, and research that investigates psychosocial and behavioral constructs should explore gender differences.…”
Section: Discussionsupporting
confidence: 80%
“…Traditionally, men are associated with a higher pain threshold, whereas women are associated with pain sensitivity. For this reason, gender is considered an important factor affecting beliefs about pain (Keogh & Boerner, 2020). The VAS scores of female patients in this study were higher than those of male patients.…”
mentioning
confidence: 49%
“…If sex and gender affect the way observers respond to those in pain, the question is whether this is due to gender-based beliefs and expectations. Empirical studies confirm the existence of stereotypical gender beliefs about pain (Bernardes, Silva, Carvalho, Costa, & Pereira, 2014;Keogh & Boerner, 2020;Keogh & Denford, 2009;Robinson, Gagnon, Dannecker, et al, 2003;Wesolowicz, Clark, Boissoneault, & Robinson, 2018;Wratten, Eccleston, & Keogh, 2019). For example, found that women are viewed as more sensitive to pain, and men less willing to report pain to others.…”
Section: Do Observers View Men and Women's Pain In A Similar Way?mentioning
confidence: 91%
“…Similarly, Wesolowicz et al (2018) found that dentists and physicians held the view that men were less willing to report pain than women. Keogh and Boerner (2020) found that the typical man is viewed as being more likely to supress pain signals, whereas the typical women is thought to be more likely to express pain through talking and crying. Other stereotypical views also exist.…”
Section: Do Observers View Men and Women's Pain In A Similar Way?mentioning
confidence: 99%